A Case Report of a Stroke Patient with Dysarthria Treated with Korean Medicine - Ji Young Baek; Yeo Bin Park; Ho-Joon Song; Ji Won Baek; Won Ho Kong; Shin-Young Kim; Chang-beom Ahn (MEDrang Inc., 2018)
This case study examined the effect of Korean Medicine on a 72-year old male with a habitual history of smoking and drinking, and a family history of hypertension who had suffered an acute stroke. A couple of months later he complained of upper extremity weakness and was diagnosed with dysarthria. The patient received Korean Medicine treatment of acupuncture and herbal medicine for 39 days at the Samse Oriental Hospital, in conjunction with physiotherapy and Western medicine. Articulation accuracy, vowel accuracy, alternation and speed of reading sentences were evaluated every 7days. The results showed that the patient had improvement of articulation (10%) and vowel (37%) accuracy, alternation (12%) and speed of reading sentences (28%) suggesting that Korean Medicine treatment contributed to this progress.